Thinking Heritage Through China - Johnston, Andrew Scott (London : Routledge, 2025)
Thinking Heritage Through China explores major themes in international heritage through the lens of heritage practice in China. China is a dynamic proving ground of heritage practice where international ideas are debated, fought over, and realized in many forms within the context of complex economic, political, and reputational forces. Preservation in China engages with many of the central themes of international heritage practice, shedding new light on considerations of authenticity and intangible heritage, politics and nationalism, and tourism and development. These forces lie at the heart of contemporary heritage practice, not only in China but also all over the world. Written by an architectural historian, architect, and heritage professional with experience in China, this book uses an architecturally and spatially focused analysis bridging critical heritage studies and the study of the built environment as shaped through heritage practice, exploring a wide range of contemporary heritage themes for a broad audience including China scholars. This book will be of interest to scholars, practitioners, and both undergraduate and post-graduate students interested in contemporary international heritage practice, heritage studies, theory and methods of heritage, comparative heritage practice, and heritage practice in China and Asia.
Keywords: China -- Civilization; BUSINESS & ECONOMICS / Industries / Hospitality, Travel & Tourism